2018
DOI: 10.5539/par.v7n1p5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Employees’ Performance through Organizational Care Policies in the Health Care Context

Abstract: Literature is increasingly recognizing that organizations must combine themes of care and concern with more established economic objectives. This conceptual study will expand on this literature by considering how expressions of organizational care toward employees, by improving their well-being, may influence their motivation, work involvement and, in turn, improve performance. In more detail, by extending the conceptual framework developed by Bonner & Sprinkle (2001), it is argued that managers should take in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Another indirect shortcut path is the mediating impact of insomnia on the relationship between night shift and job performance. The first impact on the life of night shifters is the quantity and quality of sleep (Tomo & Todisco, 2018). While performing their duty they have to sacrifice their quality of sleep because according to biological clock the most precious time for the human body to sleep is night time (Okuyan& Deveci, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another indirect shortcut path is the mediating impact of insomnia on the relationship between night shift and job performance. The first impact on the life of night shifters is the quantity and quality of sleep (Tomo & Todisco, 2018). While performing their duty they have to sacrifice their quality of sleep because according to biological clock the most precious time for the human body to sleep is night time (Okuyan& Deveci, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Costa (2010) reported that there could be many health issues associated with shift workers, which may include sleep disorders, stress, fatigue, digestive issues. These health issues also lead to psychological issues and are specifically associated with night workers (Tomo & Todisco, 2018). Employees continuously working for night shift indulge in occupational disease, injury, fatigue and insomnia which in turn reduce the working efficiencies of employees (Treuer et al, 2014;Hughes & Bozionelos, 2007).…”
Section: H2 Work Life Balance Mediates the Relationship Between Night...mentioning
confidence: 99%
“…Expressions of organizational concern for employees through policies that improve their well-being can increase employee motivation, work engagement, and performance results (Huber et al, 2015). Improving organizational performance through organizational care policies for health (Tomo & Todisco, 2018). Employee health management programs (EHMP) have an influence on organizational performance (Wolfe et al, 1994).…”
Section: ) Employee Health and Welfarementioning
confidence: 99%
“…The performance of employees can be measured by assessing the effectiveness of specific actions of employees that play their part in attaining the organizational goals. Although, motivation can be regarded as a topic of concern for both the human resource management and top managers since its impact on overall organization is noteworthy (Roy &Khastagir, 2016;Tomo & Todisco, 2018). However, the HR management and the top leaders are continuously faced with challenges; such as, lack of innovative ideas related to motivating their employees (Tomo & Todisco, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%